2012
DOI: 10.1007/s00221-012-3114-8
|View full text |Cite
|
Sign up to set email alerts
|

See what I hear? Beat perception in auditory and visual rhythms

Abstract: Our perception of time is affected by the modality in which it is conveyed. Moreover, certain temporal phenomena appear to exist in only one modality. The perception of temporal regularity or structure (e.g., the 'beat') in rhythmic patterns is one such phenomenon: visual beat perception is rare. The modality-specificity for beat perception is puzzling, as the durations that comprise rhythmic patterns are much longer than the limits of visual temporal resolution. Moreover, the optimization that beat perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
129
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 44 publications
11
129
2
1
Order By: Relevance
“…The on-the-beat and off-the-beat conditions, therefore, are analogous to the strongly metrical and weakly metrical sequences (Povel & Essens, 1985) that have been used to study the effects of metrical strength on behavioral performance. Metrical strength has been linked to improved duration discrimination performance (Grahn, 2012;Grube & Griffiths, 2009), less variable beat synchronization (Patel, Iversen, & Chen, 2005), and more accurate rhythm reproduction (Fitch & Rosenfeld, 2007). Our results suggest an explanation for why metrically strong sequences are easier to discriminate and remember: metrically strong sequences enable metrical tracking on multiple timescales simultaneously, whereas metrically weak sequences disrupt beat subdivision.…”
Section: Discussionmentioning
confidence: 69%
“…The on-the-beat and off-the-beat conditions, therefore, are analogous to the strongly metrical and weakly metrical sequences (Povel & Essens, 1985) that have been used to study the effects of metrical strength on behavioral performance. Metrical strength has been linked to improved duration discrimination performance (Grahn, 2012;Grube & Griffiths, 2009), less variable beat synchronization (Patel, Iversen, & Chen, 2005), and more accurate rhythm reproduction (Fitch & Rosenfeld, 2007). Our results suggest an explanation for why metrically strong sequences are easier to discriminate and remember: metrically strong sequences enable metrical tracking on multiple timescales simultaneously, whereas metrically weak sequences disrupt beat subdivision.…”
Section: Discussionmentioning
confidence: 69%
“…Further study of naturally hierarchical visual stimuli in hearing individuals, such as musical conducting gestures (Luck & Sloboda, 2009), dance movements (Stevens, Schubert, Wang, Kroos, & Halovic, 2009), or point-light images of biological motion (Su, 2014) could reveal whether access to metrical processing advantages is more modality-independent than previously believed. Along these lines, Grahn (2012) has suggested that for hearing individuals perception of a step-wise rotating visual bar shows evidence of metricality.…”
Section: Discussionmentioning
confidence: 99%
“…By using unimodal markers and targets in the same or different modalities, the precision of the procedure and potential temporal offsets (reflecting at least the relative processing times necessary to perceive auditory vs. visual stimuli) should be found. We expected that the precision of the aligned target position would increase with the number of auditory stimuli (marker or target), because it is reportedly more difficult to recognize visual stimulus rhythms than auditory ones (Glenberg & Jona, 1991;Grahn, 2012;Guttman, Gilroy, & Blake, 2005;Repp & Penel, 2002). Since visual rhythmic patterns activate the auditory cortex (Guttman et al, 2005), the investigation of rhythmic perception of mixed auditory and visual stimuli appears worthwhile.…”
Section: Methodsmentioning
confidence: 99%